Avaliação físico-hídrica de um latossolo vermelho em pastagem de Jiggs manejada sob diferentes intensidades de pastejo - Rupollo, Carlos Zandoná (2016)
Perennial summer pastures are an excellent forage option for livestock feed, a fact that has boosted milk production in Rio Grande do Sul. However, the lack of animal load control coupled with high grazing intensities have contributed to the degradation of pastures and loss of soil quality. The study was conducted on a farm in northern Rio Grande do Sul, and the forage used was Jiggs (Cynodon dactylon) and management method adopted was the rotational grazing, covering a 268 days production cycle. The treatments consisted of different grazing intensities in a randomized block design with four replications which the following treatments were: T1 = intensity of 0%, T2 = 30%, T3 and T4 = 50% = 70%. The experimental area was disposed within a total area of 1,760 m2, which were distributed pickets 16 (4 treatments x 4 replicates) with dimensions equal to 100 m2 each (10 x 10 m). The production of forage Jiggs had no statistical difference among treatments and the production decreases with the end of the production cycle, however, the highest concentration of leaves was found at the end of the grazing cycle influenced by plant height. There is a reduction with respect to the length and root density with increasing soil depth and the treatment one where grazing intensity was zero, had the lowest average density with respect to other treatments. The air permeability of the soil (Kar) equilibrated to tensions of 6 and 100 kPa did not reach statistical difference between treatments and the depth in the periods pre and post grazing 1. The soil layer of 0-5 and 5-10 cm was that the only influenced by the treatments in Ksat, Kar and 6 and 100 kPa, leading to a reduction in the flow of air and water in the grazing periods post 3 is 5. The grazing intensity significantly alter the soil density and macroporosity and total porosity in the 0-5 and 5-10 cm. The T1 had increasing density mean values with increasing depth, however, the treatment had decreasing average values obtained in the course of depths, where the 0-5 cm layer obtained density 1.49 g cm-3. During the grazing cycle was observed generally that the microporosity remained virtually constant. The forage production showed no statistical difference in relation to grazing intensity, the roots are concentrated in the 0-5 cm layer and cattle trampling influenced root density. In general, the grazing periods influenced Kar, Ksat and bulk density in the surface layers of the soil and the micro, macro and total porosity were mainly influenced by grazing period post 3 and post 5.